2005
DOI: 10.1359/jbmr.041107
|View full text |Cite
|
Sign up to set email alerts
|

Two Related Low Molecular Mass Polypeptide Isoforms of Amelogenin Have Distinct Activities in Mouse Tooth Germ Differentiation In Vitro

Abstract: Embryonic mouse tooth germs were cultured in vitro in the presence of two related amelogenin isoforms to determine their effects on tooth development. Our results show that these individual proteins have specific but quite different effects on epithelial-derived ameloblasts versus mesenchymal-derived odontoblasts.Introduction: Amelogenins, the main protein components of enamel matrix, have been shown to have signaling activity. Amelogenin isoforms differing only by the presence or exclusion of exon 4, designat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…However, as maturation proceeds, cell specific factors, that is factors uniquely produced by the cells themselves, come into play. We demonstrated that particular amelogenin isoforms, which are translated from distinct amelogenin gene splice products, do have signaling properties in fibroblasts and tooth germs in culture (12,13,14,15). Furthermore, we demonstrated that in tooth organ cultures, the M59/ [A−4] isoform, secreted by maturing mouse odontoblasts before the onset of dentin mineralization, had a direct affect on ameloblast terminal differentiation (14).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…However, as maturation proceeds, cell specific factors, that is factors uniquely produced by the cells themselves, come into play. We demonstrated that particular amelogenin isoforms, which are translated from distinct amelogenin gene splice products, do have signaling properties in fibroblasts and tooth germs in culture (12,13,14,15). Furthermore, we demonstrated that in tooth organ cultures, the M59/ [A−4] isoform, secreted by maturing mouse odontoblasts before the onset of dentin mineralization, had a direct affect on ameloblast terminal differentiation (14).…”
Section: Discussionmentioning
confidence: 82%
“…We demonstrated that particular amelogenin isoforms, which are translated from distinct amelogenin gene splice products, do have signaling properties in fibroblasts and tooth germs in culture (12,13,14,15). Furthermore, we demonstrated that in tooth organ cultures, the M59/ [A−4] isoform, secreted by maturing mouse odontoblasts before the onset of dentin mineralization, had a direct affect on ameloblast terminal differentiation (14). The present study was undertaken to examine whether r[A−4] binding and uptake in newborn ameloblasts involves LAMP1, as previously observed by us in an in vitro model of fibroblasts (15) In fibroblasts, r[A−4] was shown to bind to cell surface LAMP1 (15).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…amelogenin and LRAP are capable of modulating expression of cementoblast-associated genes (12)(13)(14)(15)(16). In particular, LRAPs have been shown to act differently, as signaling molecules affecting odontogenic and other cell types (12)(13)(14)(15).…”
mentioning
confidence: 99%